Potential Mutations in Chinese Pathologic Myopic Patients and Contributions to Phenotype - Chen, L.; Wei, Y.; Chi, W.; Fang, D.; Jiang, X.; Zhang, S. (Current Molecular Medicine, 2018)
Purpose: Pathologic myopia is a leading cause of visual impairment in East Asia. The aim of this study was to investigate the potential mutations in Chinese pathologic myopic patients and to analyze the correlations between genotype and clinical phenotype. Methods: One hundred and three patients with pathologic myopia and one hundred and nine unrelated healthy controls were recruited from Zhongshan Ophthalmic Center. Detailed clinical data, including ultra-widefield retinal images, measurements of bestcorrected visual acuity, axial length, refractive error and ophthalmic examination results, were obtained. Blood samples were collected for high-throughput DNA targeted sequencing. Based on the screening results, phenotype-genotype correlations were analyzed. Results: The study included 196 eyes of 103 patients (36 men and 67 women) with an average age of 52.19 (38.92 – 65.46) years, an average refractive error of -11.80 D (- 16.38 – -7.22) and a mean axial length of 28.26 mm (25.79 – 30.73). The patients were subdivided into three groups: myopic chorioretinal atrophy (190 eyes of 101 patients), myopic choroidal neovascularization (17 eyes of 15 patients), and myopic traction retinopathy (71 eyes of 61 patients). Systematic analysis of variants in the 255 genes revealed six potential pathogenic mutations: PEX7, OCA2, LRP5 (rs545382, c.1647T>C), TSPAN12 (rs41623, c.765G>T), RDH5 (rs3138142, c.423C>T) and TTC21B (rs80225158, c.2385G>C). OCA2 mutations were primarily observed in patients with myopic traction maculopathy. Conclusion: Genetic alterations contribute to various clinical characteristics in Chinese pathologic myopic patients. The study may provide new insights into the etiology of pathologic myopia and potential targets for therapeutic interventions.
Keywords: targeted sequencing